An examination of recovery planning for forest-dwelling woodland caribou (Rangifer tarandus caribou) in Ontario, Canada - Wilkinson, Christopher J. A. (Rangifer, 2008)
Ontario’s population of forest-dwelling woodland caribou is listed both federally and provincially as a species at risk. It is estimated that 20 000 woodland caribou remain in Ontario, of which approximately one quarter inhabit the boreal forest and are described as the sedentary forest-dwelling population. This paper examines the recovery strategy for this population developed by the Ministry of Natural Resources, as well as discussing the implications of provincial forestry policy on woodland caribou management. Commercial timber harvesting will likely soon be allowed in parts of the northern third of the province, in which woodland caribou habitat currently is relatively unimpaired by industrial development. Abstract in Norwegian / Sammendrag: Planlegging for bevaring av skogsøkotypen av Rangifer tarandus caribou i Ontario, Canada Skogsvillreinen av skogsøkotypen i Ontario er vurdert som sårbar både føderalt og på provinsnivå. Av provinsens rundt 20 000 skogsvillrein hører omtrent en fjerdepart til den stasjonære skogsboende skogsøkoypen. Artikkelen ser på bevaringsstrategien som er utarbeidet av naturressursdepartementet i Ontario for denne spesielle bestanden og diskuterer konsekvensene for villreinen av provinsens skogpolitikk. Kommersiell hogst vil mest sannsynlig og snart bli tillatt i deler av Ontarios nordlige tredel der skogvillreinens leveområder er relativt upåvirket av industriell virksomhet.